Barriers to Medication Adherence in HIV-Infected Children and Youth Based on Self- and Caregiver Report - Buchanan, Ashley L. (American Academy of Pediatrics, 2012)
OBJECTIVE: Nonadherence to antiretroviral therapy among children/youth with HIV often is associated with disease progression. This study examined the agreement between child and caregiver perceptions of barriers to adherence and factors associated with these barriers. METHODS: Children/youth with perinatally acquired HIV and their parents/caregivers (n = 120 dyads) completed a questionnaire about 19 potential barriers to adherence to the child’s antiretroviral therapy regimen. Agreement between the 2 reports was measured via the kappa statistic. Factors associated with the barriers were assessed by using multiple logistic regression. RESULTS: Of the 120 children, 55% were African American, 54% were boys, and the average age was 12.8 years. The most frequently reported barrier by either the caregiver or youth was “forgot.” There were varying degrees of agreement between child and caregiver on the following barriers: “forgot,” “taste,” “child was away from home,” “child refused,” and “child felt good.” Children who knew their HIV status were more likely to report logistical barriers, such as scheduling issues. Children with a biological parent as their caregiver were more likely to report regimen or fear of disclosure as a barrier. CONCLUSIONS: Lack of agreement was observed for more than half of the studied barriers, indicating discrepancies between children’s and caregivers’ perceptions of factors that influence medication-taking. The findings suggest a need for interventions that involve both child and caregiver in the tasks of remembering when to administer the child’s medications, sustaining adherence, and appropriately transitioning medication responsibility to the youth.